Intrapopulation differentiation of sockeye salmon Oncorhynchus nerka of the lake-river systems on eastern coast of Kamchatka - Anastasia M. Khrustaleva; Natalia V. Klovach (Известия ТИНРО)
Intrapopulation differentiation of the two large population systems of sockeye salmon from the Kamchatka and Apuka Rivers in East Kamchatka is considered by analysis of 45 SNP loci. Four samples were analyzed: 2 from the lower Kamchatka River (20 specimens for early run and 100 specimens for late run), 1 from the basin of Lake Azabachye belonged to the same system ( n = 81), and 1 from the Apuka River (53 specimens for mass run). No genetic differences were found between the samples for early run and late run in the Kamchatka River, though the late run sockeye could be subdivided into two genetically and morphologically different groupings, probably spawning in different biotopes: the first represented by small, fast-growing and early maturing individuals and the second represented by bigger, late maturing ones. For the Apuka River, the hypothesis was corroborated on simultaneous run of two genetically and ecologically different groupings of sockeye salmon: they differed statistically by allele and genotype frequencies of SNP loci. The intrapopulation differentiation is comparable or even exceeds the interpopulation differences for sockeye salmon of neighbor populations, though it is unobvious for geographically remote populations. This differentiation is supposedly caused by differences of natural selection in some SNP loci for different habitats.